1989
DOI: 10.1111/j.1365-2621.1989.tb08574.x
|View full text |Cite
|
Sign up to set email alerts
|

Softening of Canned Apricots: A Chelation Hypothesis

Abstract: Infiltrationof apricot (Prunu.s ameniuca L.), Patterson cultivar fruits, which are susceptible to rapid softening, with calcium chloride before processing resulted in definite firming of the canned apricots. Nonsusceptible fruits treated with citrate buffers (pH 3.7) showed dramatic post-process softening.In individual, untreated, early, green fruit, firmness after processing was directly correlated with the bound calcium:citrate ratio. Based on a chelation hypothesis, it was proposed that softening was accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 2 publications
1
8
1
Order By: Relevance
“…Firmer yellow fruit are generally preferred for canning (French, Kader, and Labavitch 1989). The improved flesh firmness in response to our biosolid applications contrasted with other reports for the Patterson variety of apricots (French, Kader, and Labavitch 1989;Southwick, Yeager, and Weis 1997). The improved firmness may have resulted from higher Ca concentration observed in the fruit harvested from our high biosolid treatment.…”
Section: Biosolid Application On Apricotscontrasting
confidence: 72%
“…Firmer yellow fruit are generally preferred for canning (French, Kader, and Labavitch 1989). The improved flesh firmness in response to our biosolid applications contrasted with other reports for the Patterson variety of apricots (French, Kader, and Labavitch 1989;Southwick, Yeager, and Weis 1997). The improved firmness may have resulted from higher Ca concentration observed in the fruit harvested from our high biosolid treatment.…”
Section: Biosolid Application On Apricotscontrasting
confidence: 72%
“…The first hypothesis, called acid hydrolysis hypothesis, suggested that organic acids, freed from vacuoles during cooking, catalyzed the hydrolysis of texture-determining cell wall constituents (Claypool, 1974;Fraye et al, 2007). For the second concept, called chelating hypothesis, softening resulted from pectin solubilization caused by chelation of wall-bound calcium by natural chelators that were released during cooking (French, Kader, & Labavitch, 1989). In our case, investigations on tissue zones physicochemical characteristics and their correlation to texture after cooking have to be done in order to explain difference in heat-susceptibility to softening observed between varieties.…”
Section: Tablementioning
confidence: 98%
“…Several studies have shown that VI improves the color of cut fruits by the impregnation of antibrowning agents (Sapers, Garzarella, & Pilizota, 1990), increases firmness of canned peaches and apricots by incorporation of calcium (Javeri, Toledo, & Wicker, 1991;French, Kader & Labavitc, 1989), improves texture and palatability of fruits (Moreno, Bugueño, Velasco, Petzold, & Tabilo-Munizaga. 2004), and reduces microbial counts of chicken meat by infiltration of acid solution into the pores of chicken skin (Deumier, 2004).…”
Section: Introductionmentioning
confidence: 98%